Transforming business with program management integrating strategy, people, process, technology, structure, and measurement - Subramanian, Satish P. (Best practices and advances in program management series, 2015)
This book illustrates a tested program management roadmap along with the supporting comprehensive frameworks to successfully execute business transformation programs, formulated strategies, and strategic initiatives. It outlines the steps to successfully transform any business and deliver tangible business outcomes. The author details the processes, techniques, and tools that a program management team can customize and easily implement on any type of strategic initiative within the private or public sector environment to deliver and sustain the expected business outcomes and benefits. It showcases program management best practices and lessons learned though real-world case studies spanning different industry sectors and functional domains.